Antenatal Microbiome: Potential Contributor to Fetal Programming and Establishment of the Microbiome in Offspring. Issue 4 (July 2015) - Wright, Michelle L.; Starkweather, Angela R.
Abstract : Background: Endogenous and exogenous exposures during fetal development have potential to impact birth and health outcomes of offspring. Accumulating evidence suggests exposures may alter the antenatal microbiome and subsequently alter the microbiome and health of offspring. Objectives: The purpose of this integrative review is to summarize and critically evaluate the current state of knowledge regarding the assessment of the antenatal microbiome on the health of human offspring. The article provides a brief summary of the known factors affecting the human microbiome and studies that assessed relationships between the antenatal microbiome and health outcomes of the offspring. Methods: An integrative review was conducted to examine human research studies that focused on the antenatal microbiome and the health of the offspring using the electronic databases PubMed/MEDLINE and CINAHL from 2004 to the present. Results: In addition to the known individual factors that are associated with establishment of the microbiome, the results of the integrative review suggest that medications (including antibiotics) and comorbidities (including infectious diseases, diet, socioeconomic status, and exposure to pollutants) should also be measured. Discussion: The composition of the antenatal microbiome at various time points and body sites may be important mediators of short- and long-term health outcomes in offspring. In order to advance our understanding of the role of the antenatal microbiome on health and disease risk of the offspring, it will be important to further elucidate the composition of a healthy microbiome and specific mechanisms that contribute to altered health in later life.